Pengaturan dan Prospek Implementasi Gugatan Perwakilan (Class Action) di Indonesia - Ramlani Lina Sinaulan (Jurnal Nuansa Kenotariatan, 2016)
Class Action is an alternative to seeking justice efforts in fighting for their rights and interests which are widely used and growing lately. Class action procedure is considered aligned with the principle of justice that is simple, quick and inexpensive. However, new alternatives are often not brought the expected results, due to hit with a variety of obstacles, mainly due to that the exclusion of class action procedure in the law of formal or procedural law. Therefore, given the importance of class action in the context development of society to respond to increasingly complex and dynamic, should the judiciary with competence can recognize, accept and implement class action in judicial practice.